Multi-Sensory and Sensorimotor Foundation of Bodily Self-Consciousness – An Interdisciplinary Approach - Ionta, Silvio; Gassert, Roger; Blanke, Olaf (Frontiers in Psychology, 2011)
Scientific investigations on the nature of the self have so far focused on high-level mechanisms. Recent evidence, however suggests that low-level, bottom-up, mechanisms of multisensory integration play a fundamental role in encoding some specific components of bodily self-consciousness, such as self-location and first-person perspective (Blanke and Metzinger, 2009). Self-location and the first-person perspective are abnormal in neurological patients suffering from out-of body experiences (Blanke et al., 2004), and can be experimentally manipulated in healthy subjects by multisensory conflicts (Lenggenhager et al., 2009). Activity of the temporo-parietal junction (TPJ) reflects experimentally induced changes in self-location and first person perspective (Ionta et al., 2011), and dysfunctions in TPJ are causally associated with out-of-body experiences (Blanke et al., 2002). We argue that TPJ is one of the key areas for multisensory integration of bodily self-consciousness, that its activity levels reflect the experience of the conscious “I” as embodied and localized within bodily space, and that these mechanisms can be systematically investigated using state of the art technologies such as robotics, virtual reality and non-invasive neuroimaging.